First Insights from On-Board Fish Gutting into the Zoonotic Nematode Burden of Pouting (Trisopterus luscus) at the Point of Sale to the Consumer - Francisco Javier Arrebola-Casañas; Mario Garrido; Francisco Javier Adroher; Rocío Benítez; Manuel Morales-Yuste (Pathogens)
A survey was conducted to assess the impact of on-board gutting in the pouting fishery, Trisopterus luscus (L.), from the Bay of Biscay (area FAO 27.VIII) on the parasite burden of macroscopic ascaridoid nematodes, including anisakids (causing anisakidosis) and raphidascaridids (causing consumer rejection) in these fish. The fish were caught in the Bay of Biscay and collected from the fish market in Granada (southern Spain). Fish larger than 25 cm were gutted on board after capture. A detailed examination of the fish revealed the presence of nematode larvae, which were identified morphologically and molecularly (PCR-RFLP: polymerase chain reaction with restriction fragment polymorphism). Results revealed that ungutted fish harbored only third-stage larvae of ascaridoids (Anisakis and Hysterothylacium) while prevalence reached up to 91%. In contrast, gutted fish exhibited a significant reduction in both the prevalence (36%) and mean abundance (MA, 4.44 vs. 0.91) of these larvae. The prevalence of Anisakis spp. larvae was reduced by over 20%, with a more pronounced reduction in abundance of more than 40% (MA, 1.56 vs. 0.91). Hysterothylacium larvae were completely absent (MA 2.88 vs. 0.00). These findings indicate that gutting, while not highly efficient, lowers Anisakis larvae presence, thereby reducing the risk of anisakiasis to consumers. Additionally, the complete removal of Hysterothylacium larvae enhances the fish’s appearance, making it more appealing and increasing its commercial value, as well as reducing the risk of seizure by health authorities. Further research on these on-board evisceration practices is needed to enhance effectiveness and reduce zoonotic nematodes in commercial fishes.